Meningkatkan Kosa Kata Benda Melalui Media Pop Up Book Bagi Siswa Tunarungu Kelas I SD di SDLB Negeri Lubuk Pakam - Lubis, Erna Maylani; Mahdi, Arisul (Jurnal Penelitian Pendidikan Khusus, 2022)
This research is motivated by the still not optimal noun vocabulary of deaf students in grade I SD at SDLB Negeri Lubuk Pakam. The purpose of this study waas to obtain data and information about the noun vocabulary of deaf students; Pop Up Book media; improve noun vocabulary through pop up book media for deaef students in grade I SD at SDLB Negeri Lubuk Pakam. The hypothesis proposed in this study is that there is an increase in the noun vocabulary of deaf students through Pop Up Book media. This research is a classroom action research with 3 students as the subject. The instrument used is a test instrument. The final results obtained by each child in cycle 1 were FA 73%, IA 53% and RA 73%, while the results obtained at the end of cycle II were FA 100, IA 87% and RA 93%. From the results of this study, it can be concluded that the noun vocabulary of deaf children in grade I SDLB Negeri Lubuk Pakam through Pop Up Books has increased well so that the Pop Up Book media is very suitable to be used as a learning medium for deaf children at SDLB Nagari Lubuk Pakam.